Aplicativo Para Estratificação De Risco E Prevenção De Tromboembolismo Venoso Em Cirurgia Plástica - Favarin, Eduardo [UNIFESP] (2018)
Background: Venous thromboembolism (VTE), defined as deep venous thrombosis and/or pulmonary embolism, is an important safety-related topic in patients undergoing surgical procedures. All preoperative patients should be carefully evaluated for risk factors for venous thromboembolism and preventive strategies should be adopted. Medical applications can be used to monitor patients, improve their treatment and assist doctors’ decision making. There are only two applications intended for plastic surgeons for VTE risk assessment but both only consider the risk factors of the patient and abstain from taking into account the procedure to be performed. Objective: To develop an a mobile-health application to assist surgeons in VTE risk stratification and prevention thrombotic events in plastic surgery. Method: The Design Thinking tool was used to create application with full participation of plastic surgeons enrolled in a professional master's degree in the four phases of the process: Discover, Define, Develop and Deliver. The application was made by a company contracted under the supervision of the author. To validate the project was used the patent method Canvas. Result: The VTE plastic surgery application was developed following Caprine Risk Assessment Score and guidelines issued by the American Society of Plastic Surgeons. It takes into account the procedure to be performed and the 39 risk factors considered by the Caprine score. Conclusion: The VTE plastic surgery application and is ready to be launched to be used by plastic surgeons aiming to prevent of VTE as a result of surgical procedures.